A Study On Financial Performance Analysis Of Xl Dynamics India Private Ltd (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
US mortgage is in growth stage of life cycle in this 21st century due to the affordable mortgage rates and increasing urbanization. US mortgage offers lower rates to makes that affordable by all citizen irrespective of the income, age, gender, race or not any. The only motive of US mortgage is to make sure all citizen in the country should have their own primary residence, that’s why the federal government allows the mortgage industry in a best way to perform. Mortgage can be segmented based on the types, interest rate, and area of property, source and the region. The source is mainly segmented as bank and mortgage companies.The purpose of this study is to analyze the financial performance of XL Dynamics India Private Limited, a private mortgage servicing company under the Sun West Mortgage Inc. The objective of the study is to analyze the financial position, scrutinizing the strength and weakness of the firm and identify the difficult of the processing in mortgage. The interpretation from this study will help the organization to know about their current position of the company and also to give suggestion in the area of development. The study has been made through secondary data available with the aid of ratio analysis and comparative balance sheet.